Kerjasama Ekonomi China-Indonesia di Era Presiden Joko Widodo sebagai Instrumen Foreign Direct Investment China - Setiawan, Sania Nusantari; Paksi, Arie Kusuma (Mahesa Research Center, 2024)
This article analyzes economic cooperation between China and Indonesia during the era of President Joko Widodo's administration in the context of Foreign Direct Investment. In the investment sector, China occupies the top three positions together with Singapore and Hong Kong as countries with the largest levels of foreign investment in Indonesia. The focus of the research includes President Jokowi's economic policy towards FDI, forms of economic cooperation between the two countries and the socio-political impact of Chinese investment in Indonesia based on the benefit principle. This research uses a qualitative descriptive approach by collecting data from various scientific literature, government policies and the latest press reports and analyzing it based on secondary data to describe the development of economic cooperation between China and Indonesia during the Joko Widodo government era. Joko Widodo's government has implemented economic policies to obtain capital. The One Stop Structured Service System and the â€œ3 Hour Investment Permitâ€ policy are significant steps. Even though there has been economic improvement, there are challenges from trade imbalances and investment problems, so regulatory policies are needed. This study concludes that Indonesia is able to improve its economy by contributing to establishing bilateral relations, as well as providing a positive impact on improving the quality of technology through Chinese FDI.